2023
DOI: 10.1002/med.21969
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive phytocompounds for oral cancer prevention and treatment: A comprehensive and critical evaluation

Abstract: The high incidence of oral cancer combined with excessive treatment cost underscores the need for novel oral cancer preventive and therapeutic options. The value of natural agents, including plant secondary metabolites (phytochemicals), in preventing carcinogenesis and representing expansive source of anticancer drugs have been established. While fragmentary research data are available on antioral cancer effects of phytochemicals, a comprehensive and critical evaluation of the potential of these agents for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 236 publications
(471 reference statements)
0
1
0
Order By: Relevance
“…Some epidemiological studies [ 30 , 31 ] have even suggested that monoterpenes might have potential applications in the prevention and treatment of cancer types, such as breast, skin, lung, colon, and prostate carcinomas. Recent research reported on the anticarcinogenic and anti-mutagenic potential of tannins [ 32 , 33 ], showcasing their ability to combat a wide range of bacteria, yeasts, molds, and viruses [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some epidemiological studies [ 30 , 31 ] have even suggested that monoterpenes might have potential applications in the prevention and treatment of cancer types, such as breast, skin, lung, colon, and prostate carcinomas. Recent research reported on the anticarcinogenic and anti-mutagenic potential of tannins [ 32 , 33 ], showcasing their ability to combat a wide range of bacteria, yeasts, molds, and viruses [ 34 ].…”
Section: Introductionmentioning
confidence: 99%